Understanding and Adherence of An Intensive Care Team to the Withdrawal of Life Support Therapy Following the Implementation of a Program for Donation After Cardiac Death. (August 2017) - Pugin, D.; Brousoz, S.; Arnaud, E.; Flatres, S.; Freitas, C.; Hechinger, S.; Rennesson, C.; Simon, J.; Moretti, D.; Gasche, Y.
Abstract : Introduction: Due to persisting shortfalls in the availability of organs for transplantation, several countries have resumed donation after cardiac death (DCD) programs. Such a program has been implemented in our institution. A multidisciplinary team had already drafted withdrawal of life support therapy(WLST) guidelines beforehand and information sessions for the intensive care team(ICT) accompanied its' implementation. Method: A survey was addressed to the ICT after 18 months to evaluate their adherence and understanding to the WLST in relation to the DCD program. Results: (table 1): 72 health care professionals participated in the survey. 76% (53/70) were nurses, 17% (12/70) doctors and 7% (5/70) nursing assistants. Their involvement in WLST was significant as 90% (65/72) reported >6 WLST in the last 5 years. On the other hand, 39% (28/72) reported to have never taken care of a brain-dead patient in the same period. 83% (60/72) were aware of the WLST guidelines and more than 58% considered it clear and appropriate. Regarding WLST, 89% (62/72) confirmed that the withdrawal of care decision was taken in patient's interest, with no consideration of DCD program. This withdrawal was occasionally considered stressful, causing irritability and a desire to cry in respectively 35%, 29% and 42% of the respondents. Moreover, 46% reported satisfaction when being able to accompany the patient to the end. The WLST was painful if a disagreement within the family or the team was present, or if the respondent felt isolated. Whereas, if the family had a good comprehension of the prognosis, or there was team collaboration >80% of the WLST were felt to have proceeded positively. 92% (62/70) of respondent considered that the pharmacological comfort care was adequate in the WLST process. In DCD program, the pharmacological comfort care was adequate for 80%. The WLST was different for 56% (39/70) of the respondents if the patient was in DCD program. The opinion of the respondents regarding the DCD program was different from the donation after brain death (DBD) program. 85% of respondents agreed with organ donation in case of DBD, while only 70% of them agreed in case of DCD. The proportion of people without an opinion doubled in case of DCD (10% vs 23%). Conclusion: WLST guidelines and information about the DCD program helps the ICU team to understand and adhere to the DCD program. The pharmacological comfort care was considered adequate; nevertheless, the WLST was different in case of DCD. This can be explained by the systematic extubation of the patient (which is not always the case in the other WLST) and his transfer to a single room for technical reasons. Adhering to the guidelines and a continuous effort on information about the DCD program is needed to help the ICT to feel comfortable with this very demanding process. Figure. No caption available.